TARI SEMUT SEBAGAI MEDIA PENGEMBANGAN KARAKTER BAGI SISWA SEKOLAH DASAR - Hartini, Hartini (Premiere Educandum, 2013)
A Â means Â of Â empowering Â studentsâ Â self-potentials Â is Â through Â art performance. Â By Â so Â doing Â they Â may Â get Â first-hand Â experience,Â knowledge, skills, creative thinking, and sense of beauty. Their sense of arts guides them to do their Â works creatively, innovatively andÂ aesthetically. Â An art performance which can be taught Â to them is dance. It helps them grow up and possess an awareness of multi-culture both locally and globally which in its turn creates actions for respect, tolerance and harmony amidst the multi-cultural society. TheÂ sort of dance taught could be those which do not require pains-taking movements, while the themes could be about plays, daily activities, orÂ animals. Semut (ant) dance is an example. Through practicing it, they not only have fun but also learn how to cooperate. Accordingly, it canÂ serve as a medium to get them develop their characters through good deeds therein. Among the characters they can learn are: (1) respectÂ and polite; (2) cooperation (gotong-royong); and (3) adaptation.Â Key words: Semut Dance, Studentsâ Character Development